Unformatted text preview: a) T ( n ) = 1 for n = 4 and T ( n ) = √ nT ( √ n ) + n for n > 4 b) T ( n ) = aT ( n1) + bn for n ≥ 2 and T (1) = 1 c) T ( n ) = 1 for n = 1 and T ( n ) = 3 T ( n 2 ) + n log n for n > 1 5. Argue that the solution to the recurrence T ( n ) = T ( n/ 3) + T (2 n/ 3) + cn is Ω( n lg n ) by appealing to the recursion tree. (For more practice and examples, read chapter 4.4 in third edition and 4.2 in second edition of the book)....
View
Full Document
 Spring '08
 Staff
 Algorithms, Recursion, Recurrence relation, following recurrence relations, recurrence evaluate

Click to edit the document details